Integrative view of 2-oxoglutarate/Fe(II)-dependent oxygenase diversity and functions in bacteria - Jia, Baolei; Jia, Xiaomeng; Kim, Kyung Hyun; Jeon, Che Ok (Biochimica et biophysica acta. General subjects, 2017)
The 2-oxoglutarate/Fe(II)-dependent oxygenase (2OG oxygenase) superfamily is extremely diverse and includes enzymes responsible for protein modification, DNA and mRNA repair, and synthesis of secondary metabolites. To investigate the evolutionary relationship and make functional inferences within this remarkably diverse superfamily in bacteria, we used a protein sequence similarity network and other bioinformatics tools to analyze the bacterial proteins in the superfamily. The network based on experimentally characterized 2OG oxygenases reflects functional clustering. Networks based on all of the bacterial 2OG oxygenases from the Interpro database indicate that only few proteins in this superfamily are functionally defined. The uneven distribution of the enzymes supports the hypothesis that horizontal gene transfer plays an important role in 2OG oxygenase evolution. A hydrophobic tyrosine residue binding the primary substrates at the N-termini is conserved. At the C-termini, the iron-binding, oxoglutarate-binding, and hydrophobic motifs are conserved and coevolved. Considering the proteins in the family are largely unexplored, we annotated them by the Pfam database and hundreds of novel and multi-domain proteins are discovered. Among them, a two-domain protein containing an N-terminal peroxiredoxin domain and a C-terminal 2OG oxygenase domain was characterized enzymatically. The results show that the enzyme could catalyze the reduction of peroxide using 2-oxoglutarate as an electron donor. Our observations suggest relatively low evolutionary pressure on the bacterial 2OG oxygenases and a straightforward electron transfer pathway catalyzed by the two-domain 2OG oxygenase. This work enables an expanded understanding of the diversity, evolution, and functions of bacterial 2OG oxygenases. •2OG oxygenases play diverse function such as biomolecular modification and synthesis.•Sequence similarity networks indicate that few 2OG oxygenases are experimentally defined.•Horizontal gene transfer plays an important role in 2OG oxygenase evolution.•Among the conserved amino acids, the primary substrates binding Tyr is not coevolved.•A Prx-2OG oxygenase catalyzes a straightforward electron transfer to degrade H2O2.